The comprehensive clinical benefits of digital phenotyping: from broad adoption to full impact - Yingbo Zhang; Jiao Wang; Hui Zong; Rajeev K. Singla; Amin Ullah; Xingyun Liu; Rongrong Wu; Shumin Ren; Bairong Shen (npj Digital Medicine)
Abstract Digital phenotyping collects health data digitally, supporting early disease diagnosis and health management. This paper systematically reviews the diversity of research methods in digital phenotyping and its clinical benefits, while also focusing on its importance within the P4 medicine paradigm and its core role in advancing its application in biobanks. Furthermore, the paper envisions the continued clinical benefits of digital phenotyping, driven by technological innovation, global collaboration, and policy support.